2022
DOI: 10.1186/s12889-022-14047-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing health and wellness by, for and with Indigenous youth in Canada: a scoping review

Abstract: Background Indigenous youth in Canada face profound health inequities which are shaped by the rippling effects of intergenerational trauma, caused by the historical and contemporary colonial policies that reinforce negative stereotypes regarding them. Moreover, wellness promotion strategies for these youth are replete with individualistic Western concepts that excludes avenues for them to access holistic practices grounded in their culture. Our scoping review explored strategies, approaches, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…The critical connection between Indigenous peoples and the environment means that climate‐induced changes can trigger emotional distress, anxiety, and a sense of loss as the very fabric of their cultural heritage is threatened (Bourque et al, 2015; Hrabok et al, 2020). Therefore, recognizing and understanding the mental health implications is crucial for designing effective strategies that address the holistic well‐being of Indigenous women, acknowledging the intricate interplay between environmental, cultural, and mental health factors (Okpalauwaekwe et al, 2022; Wexler, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The critical connection between Indigenous peoples and the environment means that climate‐induced changes can trigger emotional distress, anxiety, and a sense of loss as the very fabric of their cultural heritage is threatened (Bourque et al, 2015; Hrabok et al, 2020). Therefore, recognizing and understanding the mental health implications is crucial for designing effective strategies that address the holistic well‐being of Indigenous women, acknowledging the intricate interplay between environmental, cultural, and mental health factors (Okpalauwaekwe et al, 2022; Wexler, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While Gureje et al 1 reported on community knowledge and attitude of mental illness in the south‐west region in Nigeria using a quantitative approach, but community‐based qualitative studies at the rural level are limited. In addition, past studies on mental illness in Nigerian communities in the past four decades show that people do not have enough knowledge of mental illness 1,2 . This in turn affects people's attitudes toward those who are mentally ill in their communities.…”
Section: Discussionmentioning
confidence: 99%
“…Societal prejudice and stigma against mental illness jeopardize the delivery of high-quality comprehensive patient care and rehabilitation ( 7 , 8 ). Furthermore, negative views in society hinder mentally ill people from seeking and adhering to treatment ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%